Evaluación técnico-financiera del uso de nanomateriales en lechadas de cemento para revestimiento de producción en campo Castilla, a nivel de laboratorio (2016)
In this research, the implementation of nanosilica was raised in the cement slurry, to thereby improve the different properties of the cement slurry currently used by the Superior Energy Services company in cementing production casing in Campo Castilla. First, to know what type of cement slurry is currently being used in Castilla it was necessary to know the generalities of Campo Castilla, as its different formations, the characteristics of the rocks and the final depth of the well. Later generalities of primary cementing oil wells are described, indicating the different types and cementing practices, the additives used in cement slurries and various equipment used during the cementing process.